Non-invasive diagnosis and non-surgical treatment of endometriosis: A review - Natalia M. Podzolkova; Igor E. Fadeev; Elizaveta E. Mass; Tatiana N. Poletova; Liliana V. Sumyatina; Tatyana V. Denisova (IP Berlin A.V., 2022)
Endometriosis is a hormone-dependent condition occurring in women of predominantly reproductive age. It has an extremely diverse localization, clinical course and outcomes. The need for organ-sparing treatment to preserve and/or restore fertility, the negative effects of radical surgery for endometriosis on ovarian reserve and the effectiveness of assisted reproductive technologies, and the benign nature of the disease, which tends to self-limitation after menopause, lead to the search for effective methods of non-surgical treatment and the need for noninvasive diagnosis of endometriosis. The article presents the current principles of non-surgical management of patients with endometriosis.